2015
DOI: 10.1016/s1474-4422(14)70324-2
|View full text |Cite|
|
Sign up to set email alerts
|

Presymptomatic cognitive and neuroanatomical changes in genetic frontotemporal dementia in the Genetic Frontotemporal dementia Initiative (GENFI) study: a cross-sectional analysis

Abstract: Centres of Excellence in Neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

69
764
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 478 publications
(840 citation statements)
references
References 52 publications
69
764
2
5
Order By: Relevance
“…These regions are highly anatomically congruent with atrophy patterns found in C9orf72 ‐associated frontotemporal dementia 45, 47, 48, 49, 50. Notably, several studies confirmed that the medial thalamus is a region affected across C9orf72 expansion carriers,50 even during the presymptomatic phase 23, 36, 46. Interestingly, our subgroup analysis of presymptomatic carriers showed that higher NfL levels were associated with smaller bilateral frontoparietal and caudate volumes, which may indicate that these regions are among the earliest regions of neurodegeneration, but longitudinal presymptomatic studies are needed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…These regions are highly anatomically congruent with atrophy patterns found in C9orf72 ‐associated frontotemporal dementia 45, 47, 48, 49, 50. Notably, several studies confirmed that the medial thalamus is a region affected across C9orf72 expansion carriers,50 even during the presymptomatic phase 23, 36, 46. Interestingly, our subgroup analysis of presymptomatic carriers showed that higher NfL levels were associated with smaller bilateral frontoparietal and caudate volumes, which may indicate that these regions are among the earliest regions of neurodegeneration, but longitudinal presymptomatic studies are needed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 65%
“…In parallel with the ROI analysis, the voxel‐wise analysis showed that certain sparse regions of lower grey matter volumes tended to associate with higher poly(GP), which included regions in the bilateral dorsolateral prefrontal, medial frontal, and lateral temporal cortices. Although higher poly(GP) levels showed a relatively weak association with lower grey matter volumes in our analyses, the regions identified include those atrophied in C9orf72‐ associated FTD patients,45, 47, 48, 49 and show reduced volume in presymptomatic C9orf72 expansion carriers 23, 36…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Larger patient cohorts representing a wider range of neurodegenerative pathologies and with additional psychophysiological markers would increase power to detect physiological disease signatures; ultimately, this will require histopathological and molecular correlation. There are successful precedents for large, multi‐center studies of FTD syndromes informed by proof‐of‐principle work in intensively phenotyped patient cohorts 45. Experiments to parse the roles played by sympathetic and parasympathetic nervous systems, and the relative contribution of more basic indices of psychophysiological reactivity (such as startle and orienting responses) would further elucidate the neurobiological basis for deficits in FTD.…”
Section: Discussionmentioning
confidence: 99%